2017
DOI: 10.1097/ccm.0000000000002653
|View full text |Cite
|
Sign up to set email alerts
|

Safety Hazards During Intrahospital Transport: A Prospective Observational Study

Abstract: Findings suggest that intrahospital transport is a hazardous process for critically ill patients. We have identified several factors that may contribute to transport-related adverse events, which will provide the opportunity for the redesign of systems to enhance patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 48 publications
2
63
2
7
Order By: Relevance
“…In general, IHT is deemed hazardous in critically ill patients with common complications such as thrombosis, bleeding, or decline in pulmonary function (18). Bergman et al also reported technical hazards and equipment failure (19). Similar to our study, Martin et al focused on severe TBI patients.…”
Section: Discussionsupporting
confidence: 81%
“…In general, IHT is deemed hazardous in critically ill patients with common complications such as thrombosis, bleeding, or decline in pulmonary function (18). Bergman et al also reported technical hazards and equipment failure (19). Similar to our study, Martin et al focused on severe TBI patients.…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, the interest in studying different types of transfers in intensive care has increased (Bergman, Pettersson, Chaboyer, Carlstrom, & Ringdal, 2017;Eiding, Kongsgaard, & Braarud, 2019;Herling et al, 2020). Despite this development, interhospital intensive care unit-to-unit transfers from the family members' perspective have been sparsely investigated (Burns & Petrucka, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…We also postponed performing a CT scan of the chest as we judged patient transport to be too dangerous given the patient's clinical instability. 17 We did not expect these results to change medical management or patient outcome. The CT scan performed later on hospital day 34 showed ground-glass infiltrates, similar to those described by Miller et al At the time of this publication, there is no known treatment specifically targeting patients with ARDS associated with TMP-SMX.…”
Section: Discussionmentioning
confidence: 97%